Evaluation of positional accuracy in multiple implants using four different splinting materials: An in vitro study - Thara Maria Joseph; R Ravichandran; S Lylajam; Prasanth Viswabharan; Kavitha Janardhanan; Smitha Rajeev (Wolters Kluwer Medknow Publications, 2018)
Background: Prosthesis misfit plays an important role in complications such as occlusal and abutment screw loosening and fracture in implant restorations. Reproducing the intraoral relationship of implants through impression procedures is the first step in achieving an accurate, passively fitting prosthesis to ensure maximum accuracy. Hence, splinting of multiple implants with most accurate material may be a valid option. Context: The results of splinting multiple implants are always inconsistent, and there is limited literature available to compare the accuracy of impression techniques as well as materials. In such situation, more and more studies have to be done to prove the efficacy and accuracy of each splinting materials. Aim: The aim of the study was to evaluate the positional accuracy in multiple implants using acrylic resin, pattern resin, flowable composite, and bite registration paste. Subjects and Methods: An acrylic resin model was fabricated into which four implant analogs placed. The copings attached were splinted with dental floss onto which acrylic resin was added, which was sectioned and rewelded (Group A). Similarly, pattern resin, flowable composite, and bite registration material were added which were considered as Group B, C, and D, respectively. Impressions were made in vinyl polysiloxane and analogs were attached. The casts retrieved from each group were analysed for the positional accuracy of implants. Statistical Analysis: One-way ANOVA was done to analyze the significant difference between the four implant analogs of each group with the master model. The confidence interval was also calculated to assess the accuracy. Results: It was observed that all materials are equally effective for the accurate reproduction of implant positions. There was no significant difference between the centroids of implant analogues of master model and the mean of interimplant distance 1 and 2, 1 and 4, 3 and 4 and 2 and 4 in each group. The P-values were >0.05. The accuracy of splinting materials were analysed and it showed that splinting with flowable composite (Group C) as well as bite registration paste were in par with the conventionally used materials like pattern resin and acrylic resin. Conclusions: Results showed that flowable composite as well as bite registration material can be recommended as splinting material of choice for multiple implant cases, as these exhibited similar results like other groups (pattern resin and acrylic resin) which are conventionally used.